Pemetaan Potensi Objek Wisata Alam di Kabupaten Way Kanan Tahun 2017 - Rena Mukti Sari; Zulkarnain Zulkarnain; Dedy Miswar (JPG (Jurnal Penelitian Geografi), 2018)
This study aims to examine the potential of natural tourism in Way Kanan District. This research uses survey method, that is intended to know the potential of nature tourism in Way Kanan Regency by looking at the location, attraction, accessibility, and tourism object facilities. Data analysis technique used is descriptive analysis technique with spatial approach, and Scorring. The results of this study show that of all these objects, each object has a different attraction, facilities, and accessibility. (1) The conclusion of the attraction to the 12 natural attractions in Way Kanan District can be seen that 65% in say interesting and 35% of them in saying very interesting. (2) Accessibility to natural attractions in Way Kanan. District 65% of tourist objects can be difficult to reach while the object that is easy to reach only 30%, and the remaining 5% said to be. (3) Meanwhile, the facility can be seen that 65% in say is incomplete and 35% of them say completed.Penelitian ini bertujuan untuk menganalisis faktor – faktor penyebab anak putus sekolah jenjang pendidikan dasar di Kecamatan Ambarawa. Metode penelitian yang digunakan adalah metode deskriptif. Teknik pengukuran data yang digunakan adalah teknik analisis persentase. Populasi penelitian ini adalah 70 anak putus sekolah jenjang pendidikan dasar. Sampel penelitian ini adalah 41 anak putus sekolah jenjang pendidikan dasar beserta orang tua anak putus sekolah jenjang pendidikan dasar yang berjumlah 41 jiwa. Hasil penelitian ini menunjukkan bahwa (1) Tingkat pendapatan orang tua anak putus sekolah rendah. (2) Persepsi orang tua anak putus sekolah tentang pendidikan formal rendah. (3) Minat belajar anak putus sekolah rendah. (3) Tingkat pendidikan formal orang tua anak putus sekolah rendah. (4) Jarak tempat tinggal anak putus sekolah dengan sekolah jauh.Kata kunci : aksesbilitas, daya tarik, fasilitas pemetaan, potensi wisata alam